Experiences with a Student-Run, In-Clinic Food Donation Program for Uninsured Patients in Nashville - Nguyen, Christian; McKeon, Mallory; Ufuah , Samuel; Lloyd, Cooper; Weaver, Eleanor; Fowler, Michael; Miller, Robert (Journal of Student-Run Clinics, 2022)
Food insecurity (FI) is a dynamic and growing problem disproportionately impacting the health of minority and otherwise disadvantaged communities in the United States. Large healthcare systems address FI through screenings, community partnerships, and patient education programs. However, less has been reported on the role of small, student-run free clinics in responding to FI. Free clinics, including student-run free clinics, provide the opportunity to screen for and respond to FI with intimacy and continuity that large healthcare systems often fail to establish in these populations. Here, we aim to describe one clinic’s experience with an in-clinic, free food pantry for uninsured patients in Nashville, Tennessee. We outline the pantry’s evolution, improvement processes implemented, and data collected from July 2018 to June 2021. Data reveal that the burden of FI in our patient population is estimated as high as 80%, exceeding that of regional and national averages. While clinical associations have yet to be assessed, evidence supports the feasibility and utility of an in-clinic food pantry program for reducing the barriers to accessing healthy food in low-resource communities at high risk for FI.